PERAN TRANSPARANSI DAN AKUNTABILITAS GCG SEBAGAI GARDA TERDEPAN PENGAMBILAN KEPUTUSAN YANG ETIS - Salsabila Mahfironi; Budi Astuti Ernawati (LP2M, 2025)
This study aims to analyze the role of transparency and accountability as key elements of Good Corporate Governance (GCG) in promoting ethical decision-making in insurance companies in Indonesia. Using a quantitative approach with secondary data from annual reports and sustainability reports of insurance companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, this study employs a panel data regression model known as the Common Effect Model (CEM). The analysis results indicate that accountability has a negative impact on ethical decision-making, while transparency also shows a negative relationship but is not statistically significant. These findings indicate that overly repressive accountability mechanisms can weaken managers' moral courage in facing ethical dilemmas. Therefore, this study recommends reformulating the accountability approach and strengthening an organizational culture that promotes substantive integrity. Keyword : GCG; Transparency; Ethical Decision Making; Accountability